Hydrophilic Nasal Gel of Lidocaine Hydrochloride - Hu, Kai-Li; Mei, Ni; Feng, Liang; Jiang, Xin-Guo (Arzneimittelforschung, 2009)
Intranasal lidocaine hydrochloride (LID, CAS 73-78-9) has been widely and commonly used in the treatment of a series of symptoms such as migraine, cluster headache and trigeminal neuralgia in clinical studies. Nevertheless, rapid nasal mucociliary clearance of intranasal solution presents the predominant obstacle impacting its efficiency. In order to prolong the residence time of LID in the nasal cavity and increase its absorption, a LID nasal gel had been developed previously using hydroxypropyl methyl cellulose (HPMC) as base material. The LID nasal gel formulation has been optimized through central composite design and its in vitro release behavior has been investigated. In the present study, safety studies employing in situ toad palate model and in vivo rat nasal mucosa model showed that compared with LID nasal spray, LID nasal gel was less toxic to mucocilia. The pharmacokinetic parameters, along with olfactory and ventricle delivery of LID from nasal gel were compared with those of LID from nasal spray, intravenous injections and oral solutions in rats using microdialysis, and the drug targeting index (DTI) was used to evaluate their brain delivery. The absolute bioavailability of the optimized LID nasal gel was about 1.5 times of that of LID nasal spray which suggested a better absorption of LID from nasal gel. Moreover, the drug targeting index (DTI) of olfactory/ventricle after nasal gel and spray administration was 2.15/1.51 and 1.66/1.26, respectively. This suggested that a fraction of the LID dose could be transported directly from the nasal cavity into the central nervous system (CNS), and the brain delivery of LID can be enhanced by nasal gel.
Keywords: Brain delivery; CAS 73-78-9; Lidocaine hydrochloride; Local anesthetic; Microdialysis; Nasal gel